Larval and adult nutrition effects on reproductive traits in the red flour beetle. (3rd February 2017) - Plesnar‐Bielak, A.; Woch, K. R.; Małszycki, M. A.; Alkhawlany, A. T. H.; Hołysz, A.; Assis Correia, J. F.; Turk, N.; Ugrin, M.; Kramarz, P.; Prokop, Z. M.
Abstract: Variation in individual condition is probably one of the most critical factors affecting the high levels of diversity in animal fitness components, commonly observed in natural populations. Differential access to nutritional resources, in turn, is among the most important determinants of condition. However, our understanding of how resource access at different stages of life cycle shapes animal traits is still far from comprehensive. Here, we analyzed how larval and adult diet affects key reproductive components of males (mating activity) and females (fecundity) in red flour beetles Tribolium castaneum . Furthermore, we used path analysis to investigate whether the effects of nutritional conditions are mediated by body mass. In males, we found that juvenile, but not adult diet affected mating performance, with males developing on rich diet as larvae achieving higher mating success. In females, on the other hand, these effects interacted: malnutrition at larval stage led to fecundity decline, which was partially alleviated if dietary conditions were improved at the adult stage. Interestingly, the effects of diet on reproductive traits were mostly independent of body mass. These results suggest that larval nutrition may influence reproduction via effects on composition, rather than size, of the adult body. Abstract : This study investigated how larval and adult nutrition interact in shaping reproductive traits in male and female metamorphic insects. In red flour beetles, we found that male mating activity was affected solely by juvenile diet, whereas for female fecundity the effects of larval and adult diet interacted, suggesting that harmful consequences of juvenile malnutrition can be partially compensated for if conditions improve later in life. Interestingly, path analysis showed that diet effects on reproduction were not mediated by body size in either sex, suggesting that they act via composition, rather than size, of the adult body.